Linguistic and Terminological Complexities in Post-Editing English-Arabic Machine Translations - Eljazouli, Abderrahim; Azmi , Noureddine (International Journal of Language and Literary Studies, 2024)
The purpose of this research is to establish the challenges that professional translators face when translating using CAT and MT, particularly for the English-Arabic language pair. The research design used in the study is a comparative descriptive research design to compare different translations of source texts from English to Arabic using the SDL Trados CAT tool. The first research question is to define the most frequent types of errors in the translated texts produced by the participants of the study. The study seeks to establish some of the difficulties that translators encounter in relation to language and culture such as grammar, syntax, spelling, punctuation, style, formatting, accuracy, terminology and semantics. The research aimed to further raise awareness of these issues and how to address them in post-editing, which has been integrated into translators’ education and training to enhance productivity and the quality of the end product. The study also seeks to offer suggestions to the researchers and developers of technology in the improvement of the MT systems especially for the Arabic to English translation. The results of the analysis show that the most severe problem was observed in the syntactic and grammatical aspects of the text when translating from English to Arabic. The findings can be of benefit to developers to enhance the translation tools for efficiency, especially for Arabic to English translation.